2018
DOI: 10.1038/s41416-018-0202-y
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-stroma ratio and prognosis in gastric adenocarcinoma

Abstract: High proportion of stroma is an independent prognostic factor in both intestinal and diffuse histological subtypes of gastric adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 18 publications
4
80
0
Order By: Relevance
“…Recently, increasing attention has been focused on the association between tumor microenvironment and the prognosis of cancer, such as breast cancer and gastric adenocarcinoma . It is noticeable that infiltrating immune cells have been associated with tumor growth, invasion and metastasis in some cancers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, increasing attention has been focused on the association between tumor microenvironment and the prognosis of cancer, such as breast cancer and gastric adenocarcinoma . It is noticeable that infiltrating immune cells have been associated with tumor growth, invasion and metastasis in some cancers .…”
Section: Introductionmentioning
confidence: 99%
“…6 Recently, increasing attention has been focused on the association between tumor microenvironment and the prognosis of cancer, such as breast cancer 7 and gastric adenocarcinoma. 8 It is noticeable that infiltrating immune cells have been associated with tumor growth, invasion and metastasis in some cancers. 9,10 In accordance with these findings, Ali et al 11 revealed that immune infiltration is associated with clinical prognosis of breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…As the stromal proportions were correlated with the expression of the methylation-driven key regulators in the G1 group, they were significantly associated with poor survival in multiple showing poor survival associated with higher tumor-stroma interactions [30][31][32] .…”
Section: Influence Of Tme On the Methylation-driven Key Regulatorsmentioning
confidence: 98%
“…Tumor-stroma interactions in GC are associated with prognosis [30][31][32] and contribute to molecular heterogeneity 21 . Hence, we investigated whether variations of the methylation-driven key regulators were from tumor cells or associated with TME.…”
Section: Tumor Intrinsic Variations Of the Methylation-driven Key Regmentioning
confidence: 99%
See 1 more Smart Citation